Anatomical and surgical bases of frenotomies - Mate, Miguel; Bonilla, Conrado; Campos, Néstor; Servetti, Eduardo; Cazabán, Luis A (Cirugía del Uruguay, 1973)
Post-mortem and experimental research work aimed at demostrating the topography of the different anatomical elements which condition a satisfactory phrenotomy, is reported by the author. The intradiaphragmatic distribution of the phrenic nerve and its cascular connections are analyzed. The author differentiated between elective phrenotomies and politraumatized patients. The value of diaphragmatic wounds as approach for exploratory purposes is discussed and limitations thereto are established